1981
DOI: 10.1128/jb.146.1.155-162.1981
|View full text |Cite
|
Sign up to set email alerts
|

Control of membrane lipids in Mycoplasma gallisepticum: effect on lipid order

Abstract: Adaptation of Mycoplasma gallisepticum, a sterol-requiring Mycoplasma sp., to growth in a serum-free medium supplemented with cholesterol in decreasing concentrations and with various saturated or unsaturated fatty acids enabled us to control both the cholesterol levels and the membrane fatty acid composition. An estimate of the membrane physical state from fluorescence polarization of 1,6-diphenyl-1,3,5-hexatriene indicated that the membrane lipids of native M. gallisepticum were highly ordered. Elongation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Nevertheless, this limited growth is sufficient to study molecular organization and physical properties of media is due to the presence of phospholipids in serum, which are directly incorporated into membranes by the growing mycoplasmas. The growth curves observed for M. canadense and M. verecundum in the serum-free media are similar to those reported in the literature for other mycoplasmas (1,2,6,14). Growth in agar plates incubated in a humid atmosphere resulted in formation of colonies with the characteristic fried-egg morphology in agar supplemented with horse serum and in the serum-free agar plates, as can be seen for M. canadense in Fig.…”
supporting
confidence: 87%
“…Nevertheless, this limited growth is sufficient to study molecular organization and physical properties of media is due to the presence of phospholipids in serum, which are directly incorporated into membranes by the growing mycoplasmas. The growth curves observed for M. canadense and M. verecundum in the serum-free media are similar to those reported in the literature for other mycoplasmas (1,2,6,14). Growth in agar plates incubated in a humid atmosphere resulted in formation of colonies with the characteristic fried-egg morphology in agar supplemented with horse serum and in the serum-free agar plates, as can be seen for M. canadense in Fig.…”
supporting
confidence: 87%
“…The toxicity of ethanol was ruled out since we found that the amounts incorporated were not inhibitory to these mycoplasmas. In contrast, LeGrimellec et al were able to grow M. gallisepticum in serum-free modified Edward medium containing an ethanolic cholesterol suspension (8). However, the basal compositions and supplements of the two formulations differ.…”
Section: Discussionmentioning
confidence: 93%
“…However, some Mycoplasma species have been grown with serum-free media when the transport, composition, and fluidity of mycoplasma membranes were being investigated (4,8,12). Kahane and Razin (7) showed that liposomes can serve as a carrier of cholesterol; however, their experiments were completed within 17 to 24 h, mycoplasma growth was estimated by measuring changes in optical density, and the organisms were not serially transferred in serum-free medium.…”
mentioning
confidence: 99%
“…Replacement of serum with defatted albumin, sterols, phospholipids, and fatty acids (5,23) has greatly simplified the composition of the growth medium. These substitutions are particularly helpful for investigations of mycoplasma lipid metabolism (7) and membrane chemistry (12,18), cases in which a defined lipid composition is essential.…”
mentioning
confidence: 99%